2019
DOI: 10.1177/1468796819866351
|View full text |Cite
|
Sign up to set email alerts
|

More open borders for those left behind

Abstract: Including the interests of those migrants leave behind in debates about migration and justice is a strategy which theorists who are sceptical of open borders have made use of, most notably in brain drain critiques of emigration. In rejecting this view, and in invoking an epistemic conception of liberalism, I claim that not only can the interests of those left behind be appealed to by defenders of more open borders. For at least two reasons such interests should be included. First, more open borders have a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The results showed that motivation, re-migration strategies, job opportunities, and minimum wage are the most influential reasons for Laotian re-migrants to polarized post-COVID-19 Thailand. This finding is consistent with Ikotun et al (2021) and Tebble (2020), indicating that the reason for re-migration is the continuing era of reopened borders after the COVID-19 pandemic, due to its benefits. Our results also support previous studies which showed that many reasons for re-migration strategies, such as agency-facilitation, host country wages, and aspiration, may reinforce cross-border mobility (Daovisan et al, 2022; Hayakawa et al, 2022; Suhardiman et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…The results showed that motivation, re-migration strategies, job opportunities, and minimum wage are the most influential reasons for Laotian re-migrants to polarized post-COVID-19 Thailand. This finding is consistent with Ikotun et al (2021) and Tebble (2020), indicating that the reason for re-migration is the continuing era of reopened borders after the COVID-19 pandemic, due to its benefits. Our results also support previous studies which showed that many reasons for re-migration strategies, such as agency-facilitation, host country wages, and aspiration, may reinforce cross-border mobility (Daovisan et al, 2022; Hayakawa et al, 2022; Suhardiman et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Individual actors, therefore, can be said to participate in the transformation of deep structure, even if often only accidentally so. It is also with this epistemic understanding in mind that I (Tebble, 2018) advance an argument for freedom of movement between states because of the intended, and crucially unintended, poverty alleviating effects of immigrant remittances.…”
Section: Prelude To a Liberal Response: Erik Olin Wright And Interstimentioning
confidence: 97%
“…Those decisions have regularly been justified based on maintaining state sovereignty but can also be seen as processes of (re)territorialization (Vigneswaran, 2013). Political philosophy at this stage remains divided about the ethics of borders (Bartram, 2010; van Houtum, 2012; Genova, 2017; Paasi et al, 2018; Tebble, 2020), with strong arguments being made in favor of open borders (Bartram, 2010). In this article, we cannot resolve those debates.…”
Section: The Border Control Contextmentioning
confidence: 99%